EXCLUSIVISM AND PLURALISM DIALECTICS ON THE RELIGIOUS MODERATION IN INDONESIA - Robbin Dayyan Yahuda (Proceeding of Conference on Strengthening Islamic Studies in The Digital Era, 2023)
ABSTRACT: The trend of religious moderation studies in Indonesia is experiencing practical factual problems, where the differences between exclusivism and pluralism influence the interpretation of religious moderation in Indonesia. Adherents of exclusivism influence various moderation in Indonesia towards radicalism, extremism and terrorism. Pluralism adherents acquire religious moderation towards secularism, liberalism and atheism. Thus, need steps to bridge the differences between these ideologies. This paper discusses the dialectic of exclusivism and pluralism in religious moderation in Indonesia. Using a qualitative method, this paper analyzes the dialectical problem of exclusivism and pluralism in the theological and social realms. data analysis using content analysis method through a data reduction process, data display and conclusion. The results of the dialectical analysis of exclusivism and pluralism in the theological realm produce religious moderation inclusivity, while in the social realm it produces religious moderation inclusivism. The concepts of inclusivity and inclusivism create relational harmony between exclusivism and pluralism in religious moderation in Indonesia.